Impact of Digital Word of Mouth (D-WOM) on Consumer Behavior: The Evolution of Online Shopping and Its Impact on Consumer Behavior (Journal of Advances and Scholarly Researches in Allied Education, 2021)
With the development of net, the fashion of purchasing has changed amongst consumers. The technological advancements like smart phone and 4G internet have opened new avenues for online shopping. The consumers are shifting their purchases from offline to on line mode the usage of Electronic trade. Marketing may be there all the time in one form or other. Since, the day while people first started out trading by any means it changed into that they first traded, marketing become there. Marketing changed into the stories they used to convince different human beings to change. Humans have come a long way on account that then, and advertising has too. The manner of execution of advertising is transformed and progressed every day. The evolution of net in the global bringing lot greater adjustments in the society specifically in living style of human beings. As the wide variety of net users is developing everywhere in the world in which people are greater attached to the digital devices like computers, laptops, cell phones etc. The data available at the net platform permits the human beings to get entry to from any nook of the arena.